A new brachypterous species of Elachiptera Becker (Diptera: Chloropidae) from freshwater wetlands in eastern Canada - Wheeler, Terry A. (Zootaxa, 2003)
Elachiptera aquila sp. nov. is described from freshwater wetlands in Ontario and Quebec, Canada. Its apparent sister species is Elachiptera salinaria Sabrosky and Valley, known from coastal salt marshes in the eastern United States. Although there are Palearctic Elachiptera that are polymorphic for wing length, this is the first brachypterous species of the genus described from North America.